Masculinidades possíveis em um grupo de homens apenados pela lei Maria da Penha - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
The research aims to analyse the discursive practices of men punished by Maria da Penha Law, in reason of the practice of domestic and family violence against women, referred for a reflective group, according to the articles 35 and 45 in the same law. Taking references on Cultural Studies, the research search to relate speeches from a possible hegemonic pattern of masculinity with the practice of domestic and family violence against women, and identify new meanings in the speeches of these men due to of them participation in reflective group. The research is documental and the corpus consists in written material, resulting from de-recording the speeches of participants. Additional informations were drawn from the file of the criminal proceedings, consulting to the police reports, judgment and other documents in order to determine the profile of the participants of reflective group. The work is organized from the exposure of informations about the study group, as the format of carrying out of meetings, the facilitators, the strategies and rules, the difficulties of de-recording, the profile of participants, the ethical issues and some methodological possibilities of working with groups men. After that, it presents the legislative developments, statistics data and public policies developed in confronting of domestic and family violence against women in Brazil. It articulates theoretical notes about the reflexive groups with the speeches of the participants men of the research group in order to demonstrate how participants men perceive their referral to the reflexive group. Based on the concept of identities, it relates the search for the pattern of hegemonic masculinity, unattainable for the vast majority of men, one of the causes of this such violence; behiond it there are men‟s perceptions about the reflection process developed inside the group. The main results point to the importance of the work of reflective groups of men to confronting of violence against women as an effective way of deconstructing masculinities closely related to violence, and a hegemonic, heteronormative and patriarchal model. On the other hand, emerges the problem of violence used by both partners as a means of conflict resolution, which implies the need for treatment the phenomenon in a relational bias.
Keywords: grupo reflexivo; identidades; Lei Maria da Penha. masculinidades. violência doméstica e familiar contra a mulher; reflexive group. identity. Maria da Penha Law. masculinities. domestic and familiar violence against woman; CNPQ::LINGUISTICA, LETRAS E ARTES::LINGUISTICA